2011
DOI: 10.1536/ihj.52.212
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Amiodarone Therapy for the Prevention of Recurrence of Paroxysmal Atrial Fibrillation Analysis Based on Patient Characteristics

Abstract: SummaryThere is little information available on factors affecting the long-term prevention of paroxysmal atrial fibrillation (AF) in the Japanese population. A total of 71 patients (49 men, mean age, 68 ± 8 years) with paroxysmal AF refractory to ≥ 2 class I antiarrhythmic drugs received oral amiodarone (50-200 mg/day). All patients were observed for more than 12 months (mean follow-up period, 47 ± 26 months) and were analyzed on the basis of patient profiles. The percentage of patients with AF recurrence desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(32 reference statements)
0
3
0
2
Order By: Relevance
“…Oral AMD is effective for refractory atrial fibrillation (AF). [1][2][3][4][5] Although serious lung injury such as interstitial pneumonia (IP) occasionally occurs (10%), the mortality rate is 2%. 2,6) In recent years, the administration of AMD has increased in AF patients, and serious complications such as interstitial pneumonia (IP) occasionally occur.…”
mentioning
confidence: 99%
“…Oral AMD is effective for refractory atrial fibrillation (AF). [1][2][3][4][5] Although serious lung injury such as interstitial pneumonia (IP) occasionally occurs (10%), the mortality rate is 2%. 2,6) In recent years, the administration of AMD has increased in AF patients, and serious complications such as interstitial pneumonia (IP) occasionally occur.…”
mentioning
confidence: 99%
“…It is likely that the wide variability in the percentage of patients successfully treated with antiarrhythmic drugs was caused by differences in patient profiles among the studies. It has been suggested that recurrence of AF is associated with aging [19,20], duration of AF episodes [21,21], AF history [23], increased left atrial dimension [21,22,24], the presence of underlying heart disease (e.g., valvular and ischemic heart diseases) [21,25], and circadian variation in AF onset (mixed AF type) [26], among other factors. Moreover, patients in Western countries receive different types of antiarrhythmic drugs at doses 1.5-to 2-fold higher than the standard doses in Japan.…”
Section: Results Of Studies In Western Countriesmentioning
confidence: 99%
“…Все эти известные в настоящее время нейрогуморальные механизмы снижения АД участвуют также в патогенезе ФП [14]. Большинство исследований влияния физической нагрузки на сердечно-сосудис тую систему проведено использованием АН [8,9], и имеется только несколько исследований с применением РН [10].…”
Section: Discussionunclassified
“…Физическая активность -одна из главных компонентов лечения АГ [8]. В исследованиях, посвященных профилактике и лечению сердечно-сосудистых заболеваний в основном применялся аэробный тип нагрузки (АН) [9,10]; сравнительно недавно началось исследование влияния резистивной нагрузки (РН), т. е. с отягощениями, на профилактику и течение сердечно-сосудистых заболеваний [11].…”
Section: Introductionunclassified